Western Influences in the Early Christian Architecture of the Northern Balkans - Obraztsova, Ksenia B. (Actual Problems of Theory and History of Art, 2024)
The article presents an overview of Early Christian churches of the Northern Balkans. The emphasis is placed on architectural features and liturgical equipment that could be associated with one of the regional traditions known for the area in order to trace political and cultural influences. The Northern Balkans are divided in the study into three parts — Greek-speaking territories of the Eastern Illyricum, the coast of the Adriatic sea and the Latin-speaking provinces of the Northeast. The main issue for the study was the question of limits that Roman influence gained in the Balkans. The area belonged to the jurisdiction of the Roman cathedra for the whole Early Christian period, so the regional building tradition was expected to be determined by the West. However, the forms and extents of alleged control, uneven in various Balkan provinces, remain questionable. Our research shows that no distinct traces of Roman impact can be revealed in liturgical arrangement of churches in this region. The Northern-Greek buildings seem to follow a local version of the Constantinopolitan tradition. The Latin-speaking areas were affected by the intense impact of the capital only in the 6th century. It took diversified forms depending on the routes of distribution coming directly from Constantinople or indirectly via Ravenna or Justiniana Prima. The buildings of the 5th century in the Adriatic zone demonstrate the greatest isolation from the capital, however, they follow the Northern Italian rather than Roman tradition. Yet there are examples of anomalous features in every region, that can be associated with isolated centers of Roman, Dalmatian or Greek presence. This work is supported by the Russian Science Foundation (grant 20-18-00294-P) and done at the Research Institute of Theory and History of Architecture and Town Planning — branch of the Central Research and Project Institute of the Construction Ministry of Russia.